Law as a Method for Defining Social Life in the Successful Society; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Zhuravlev S. V. (2017, 2017)
Title screen